La bioética bajo el contexto del VIH/Sida - Gil , César Augusto Ugarte (Brazilian Journal of Sexually Transmitted Diseases, 2005)
From the beginning of the epidemics, HIV/AIDS is showing to be a complex issue in individual and social aspects due to multiple factors: social, economic and political. These factors lead to the implementation of discussion and research efforts, setting up a new action scenery. A field that hasbeen much discussed and studied, with the participation of scientists, activists and health authorities, is the field of Bioethics. Many aspects were con-sidered. Among them therapeutic and epidemiologic research methods and care giver-patient relationship and treatment options. In this context, it isimportant to apply all accumulated experiences, discuss them and integrate them in the development of new studies, provision of care, developmentand implementation of public health policies as well as in the training of new healthcare providers.